Aptitude for Destruction, Volume 2 - Jackson, Brian A.; Baker, John C.; Chalk, Peter; Cragin, Kim; Parachini, John V. (RAND Corporation, 2023)
Better ways are needed to understand how terrorist groups increase their effectiveness and become more dangerous. Learning is the link between what a group wants to do and its ability to actually do it; therefore, a better understanding of group learning might contribute to the design of better measures for combating terrorism. This study analyzes current understanding of group learning and the factors that influence it. It presents detailed case studies of learning in five terrorist organizations and develops a methodology for ascertaining what and why groups have learned, providing insights into their learning processes.